Quality Management System: Analisis Raport Mutu Usaha Kesehatan Sekolah (UKS) - Sapto Irawan; Danu Prasetyo (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Kristen Satya Wacana, 2020)
This quality report analysis was conducted to see the quality achievement of SMK PGRI 1 Salatiga in one year for School Health Efforts (UKS) in 2018. This research describes descriptively both qualitatively and quantitatively the results of the quality report card achievement. It was shown that the achievement score in the School Health Business Report Card (UKS) was 6.6 with the category of UKS 4. Referring to the results of the analysis of the description above, it showed that the achievement report had obtained the four-star category. Validation of the achievement of the School Health Effort report card (UKS) is needed to show the real condition of the school. The achievement of the four-star category is strongly influenced by two important factors in its implementation, namely: 1) the awareness of all school members to realize a healthy lifestyle; 2) the facilities and infrastructure support in realizing healthy living behavior.